Predictive value of heart rate for prognosis in patients with cerebral infarction without atrial fibrillation comorbidity analyzed according to the MIMIC-IV database - Xinrou Song; Luwen Zhu (Frontiers in Neurology)
ObjectiveThis study focused on the relationship between heart rate and the likelihood of death within 28 days in patients with cerebral infarction without the comorbidity of atrial fibrillation, using patient data extracted from the MIMIC-IV database.MethodThis study involved a retrospective analysis of clinical data from 1,643 individuals with cerebral infarction who were admitted to the ICU. To investigate the role of heart rate in determining patient survival, we applied a variety of statistical techniques such as Cox regression models, survival analysis using Kaplan–Meier plots, and spline-based models. In addition, we performed analyses by patient subgroups to identify any potential variables that could influence the association between HR and 28-day mortality.ResultIn univariate and multivariate analyses, elevated heart rate was strongly associated with higher 28-day mortality, even after adjusting for confounders such as age, sex, comorbidities, and clinical scores.(HR:1.01, 95%,CI:1.01 ~ 1.02, p = 0.019) Kaplan–Meier survival analysis showed that patients with heart rate > 90 beats/min had a significantly lower probability of survival. Restricted cubic spline (RCS) analysis confirmed a nonlinear relationship between heart rate and mortality. Subgroup analyses demonstrated an interaction between heart rate and factors such as hypertension and mechanical ventilation status.ConclusionThis study highlights the prognostic significance of heart rate as an independent predictor of 28-day mortality in patients with cerebral infarction who do not have atrial fibrillation.